ANALISIS PENGARUH KINERJA KEUANGAN PERBANKAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Hidayah, Roisatul; Sakti, Rachmad Kresna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Financial performance is an illustration of the level of success achieved by a bank in its operational activities. banking financial performance is a major factor and is very important to assess the overall banking performance by looking at the value of the company. The purpose of this study was to determine the effect of CAR, NPL, LDR and BOPO on firm value with profitability as an intervening variable in banking companies. This type of research is quantitative research. As for the sample used in this study, namely 8 bank financial reports published during the 2012-2021 period using the random sampling method. The data analysis technique used is multiple linear regression and Moderrated Regression Analysis (MRA). The results of the study state that CAR and NPL have no effect on firm value, while LDR and BOPO have a negative and significant effect on firm value. In addition, the results of this study also state that profitability is proven to be able to moderate the relationship between the influence of CAR, NPL, LDR and BOPO on firm value. It is hoped that banking management can focus more on improving the performance of the Loan to Deposit Ratio (LDR) and BOPO (Operating Costs to Operating Income), this is because during the study period these variables had a negative and significant effect on Price to Book Value (PBV). Besides that, banking companies also need to pay attention to their profitability. Because profitability is a picture of banking in obtaining profits.